Validation of modified shear buckling coefficients for horizontally curved steel plate girders. (May 2020) - Frankl, Bernard A.; Linzell, Daniel
Abstract: Steel plate girders are an attractive choice for horizontally curved geometries because they can be efficiently designed to resist the torsional stresses induced from the curvature. The effects of horizontal curvature on flexural behavior have been extensively studied. However, the behavior and design of horizontally curved, steel, plate girders under shear is still treated as if they were straight. It is of interest to examine the effects of horizontal curvature on plate girder shear strength because it could offer increased shear capacity. A series of companion studies were completed to examine if horizontal curvature increased shear capacity and to develop shear buckling coefficients that accounted for curvature. Summarized herein are steps taken to develop shear buckling coefficients that incorporate horizontal curvature in a form that would be easily adaptable to current American design specifications. Two different coefficients are proposed, the first a simple, curve fitting approaches based on work first published by Batdorf in 1947 and the second derived using energy based approaches that expand on classical work published by Timoshenko and Gere. The accuracy with which the proposed coefficients predict horizontally curved, plate girder shear response was examined via comparison between predicted shear buckling limits and ultimate capacities against values obtained from calibrated finite element models. These comparisons show that shear buckling capacity is enhanced when horizontal curvature is correctly accounted for in shear buckling coefficient derivations, which can enhance plate girder buckling capacity and, in turn, shear strength. Highlights: This document presents two shear buckling coefficients that account for horizontal curvature for steel plate girders with slender webs. This document calibrates the Timoshenko and Gere's modified shear buckling coefficient against a series of calibrated FEM and reformats the coefficient to a format consistent with current design code equations. The shear buckling capacity and ultimate shear strength, calculated with each proposed shear buckling coefficient, are compared against the calibrated FEMs across a varied range of horizontal curvatures, web slenderness ratios and panel aspect ratios. It is found that both modified shear buckling coefficients produce improved shear buckling capacities as well as ultimate shear strengths. The modified Timoshenko and Gere's shear buckling coefficient produces shear strengths up to 65% more accurate than estimating assuming straight panels as is used in current practice.